Virtual Colonoscopy A Practical Guide - Lefere, P.; Gryspeerdt, S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Virtual colonoscopy, or CT colonography, is a rapidly evolving technique for the detection of tumoral lesions in the colon. It is now accepted by the American Cancer Society as a valuable screening tool for both colorectal cancer and its adenomatous precursor. Virtual colonoscopy requires state-of-the-art technique with rigorous preparation, colonic distension, and optimization of scanning parameters. Dedicated reading, analysis, and reporting of the data sets are mandatory. With contributions from a number of leaders in the field, this book addresses all the important issues relating to virtual colonoscopy. There is a particular focus on practical aspects: how to start virtual colonoscopy in your department, the regular preparation, the importance of fecal tagging, how to reduce the preparation, how to obtain optimal colonic distension, and the correct scanning parameters. Imaging characteristics and pitfalls are considered in detail, with an extensive pictorial review of difficult lesions; the importance of computer-aided diagnosis is also discussed. In this second edition the text has been updated with the latest study results and developments in technology and new illustrations have been included. This book will be invaluable to every radiologist seeking information on how to perform the exciting technique of virtual colonoscopy.
Why We Do CTC: Screening for Colorectal Cancer -- The Performance of CTC -- Starting CT Colonography in Your Department -- The Eligible Patient: Indications and Contraindications -- Patient Preparation for CT Colonography -- The Prerequisite: Faecal Tagging -- How to Get the Colon Distended? -- Right Parameters -- How to Interpret CTC Data: Evaluation of the Different Lesion Morphologies -- How to Avoid Pitfalls in Imaging: Causes and Solutions to Overcome False-Negatives and False-Positives -- 3D Imaging: Invaluable for the Correct Diagnosis? -- The Challenge: Detection of Early-Stage Superficial Colorectal Lesions -- Extracolonic Findings -- The Future: Computer-Aided Detection -- Quality and Consistency in Reporting CT Colonography -- Virtual Colonoscopy: Beyond Polyp Detection -- Pictorial Overview of Normal Anatomy, Mimics of Disease, and Neoplasia Using CT Colonography.
Keywords: Medicine; Radiology, Medical; Internal medicine; Gastroenterology; Oncology; Endocrinology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Gastroenterology; Internal Medicine; Proctology; Oncology